Embodying the Other, Preparing the Self: Impersonation Technique as Simulation-Based Pedagogy for Communicative Skill Development and Workforce Readiness - Herditya Wahyu Widodo; Mochamad Nasrul Chotib; Kukuh Prayitno Subagyo; M Misbahul Amri; Suhono Suhono (Pusdikra Publishing, 2026)
This study investigates the use of impersonation technique to enhance ten communicative skills essential for workforce readiness: active listening, confidence, appropriate method selection, tone and volume control, empathy, friendliness, respect, feedback-sharing, non-verbal cue interpretation, and responsiveness. Employing a mixed methods design within a four-day intensive workshop, quantitative data were collected from 77 performer-participants (actors, actresses, directors) via structured questionnaires, while qualitative insights were obtained through an interview with an expert drama practitioner. The findings revealed that 92.72% of respondents reported experiencing the target skills during the preparation and performance phases, and 95.58% perceived these skills as beneficial for their future careers. Notably, a gap emerged between the experience (87%) and perceived utility (94.8%) of non-verbal cues and responsiveness, interpreted through the lens of tacit knowledge-learners enacted these skills without full conscious awareness. The expert interview further illuminated the phase-specific nature of skill development, identifying respect and feedback-sharing as dominant during collaborative preparation, confidence and non-verbal reading as prominent on stage, and vocal modulation and active listening as operating across both phases. The study concludes that impersonation technique functions as a form of simulation-based and transformative learning, cultivating regulative skills during preparation and expressive skills during performance. This positions impersonation as a promising and adaptable pedagogy for bridging the soft skills gap in higher education, though longitudinal research on actual skill transfer to workplace contexts remains a priority for future investigation.